THEORETICAL ASPECTS OF ENGLISH LANGUAGE - Kasimova Adiba Nasirovna; Seytbekova Aynura (TADQIQOTLAR, 2025)
This article explores the nature, functions, and significance of stylistic devices and expressive means in the English language. The purpose of the work is to analyze how various linguistic tools enhance communication, influence readers and listeners, and contribute to the aesthetic and emotional tone of texts. The study highlights the role  of  figurative  language,  sound  patterns,  and  syntactic  structures  as  essential components  of  stylistic  expression.  It  also  demonstrates  how  understanding  these elements  improves  the  ability  to  interpret  literary  works  and  enhances  overall communicative  competence.  The  article  is  intended  for  students,  researchers,  and anyone interested in deepening their knowledge of English stylistics.